2022
DOI: 10.3389/fimmu.2022.975921
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbes in cerebrovascular diseases: Gut flora imbalance, potential impact mechanisms and promising treatment strategies

Abstract: The high morbidity, mortality, and disability rates associated with cerebrovascular disease (CeVD) pose a severe danger to human health. Gut bacteria significantly affect the onset, progression, and prognosis of CeVD. Gut microbes play a critical role in gut-brain interactions, and the gut-brain axis is essential for communication in CeVD. The reflection of changes in the gut and brain caused by gut bacteria makes it possible to investigate early warning biomarkers and potential treatment targets. We primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 176 publications
0
18
0
Order By: Relevance
“…Intestinal T cells develop protective activity following transplantation of feces from a young population into mice with IS. Treg cells and IL-17 T cells contribute to decreased inflammation, neurological deficits, and impairment of intestinal barrier function following stroke (Lee et al, 2020;Haak et al, 2021;Zou et al, 2022). In mice with ICH, transplantation of bacterial flora can affect T cells in the brain, reduce neuroinflammation following bleeding, and restore the average fluorescence intensity of the tight junction proteins occludin and claudin-1, thereby restoring intestinal barrier function (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal T cells develop protective activity following transplantation of feces from a young population into mice with IS. Treg cells and IL-17 T cells contribute to decreased inflammation, neurological deficits, and impairment of intestinal barrier function following stroke (Lee et al, 2020;Haak et al, 2021;Zou et al, 2022). In mice with ICH, transplantation of bacterial flora can affect T cells in the brain, reduce neuroinflammation following bleeding, and restore the average fluorescence intensity of the tight junction proteins occludin and claudin-1, thereby restoring intestinal barrier function (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, research has uncovered the function of microbiomes in varieties of diseases, mainly including cancer immunotherapy (Li et al, 2019), systemic inflammatory diseases (Clemente et al, 2018), and cardiovascular system diseases (Jie et al, 2017). Recent studies have revealed that the gut microbiota has evolved into an inseparable and symbiotic relationship with the host during the evolutionary process (Zou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In general, ICH produces more severe strokes than cerebral infarct ( 66 , 67 ). ICH typically manifests as elevated intracranial pressure, hematoma compression, and serious cerebral edema, which can cause many negative effects, such as neuroinflammation, mitochondrial dysfunction, and apoptosis, resulting in a sudden disruption of the blood–brain barrier ( 68 ). Contrary to ICH, the structural stability of brain cells and the blood–brain barrier is retained for a longer length of time following the beginning of symptoms in ischemic stroke ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the possible causes of stroke complicating gastrointestinal motility disorder-related disease. Moreover, the change in gut microbes caused by intracerebral hemorrhage may be one of the causes of some gastrointestinal diseases ( 68 ). A prospective case–control study found that compared with the control group, the intestinal microbiota composition of both patients with ischemic stroke and patients with intracerebral hemorrhage changed ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Every 6 seconds, one person in the world dies of stroke (2,3), and 60%-80% of these cases are due to ischemic stroke (4). Recent studies have demonstrated that stroke has a strong inflammatory response, intestinal symbiotic bacteria regulate ischemic stroke injury, and there is two-way communication between the brain and the gut called the "Microbiome-Gut-Brain Axis" (MGBA) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%